"I'm a foreigner there": Landscape, wellbeing and the geographies of home. (March 2020) - Wood, Naomi; Martin, Daryl
Abstract: The experience of migration brings particular challenges for wellbeing, especially as an individual's sense of disconnection from previous homes can persist over many years. This paper reports on how visitors to a Chinese community centre in NW England reflected upon their experiences of being uprooted from their homelands, even in cases where they had lived for more than half of their lives in the UK. Memories of their previous homelands were persistently called upon in understanding their sense of belonging and cultural identities in the present. We use their accounts in dialogue with recent theories of landscape, especially those that argue for an understanding of place as embodied, ambivalent and in a continual process of making and re-making, in order to trace memories of home in contemporary cultures of wellbeing. Highlights: Memories of homelands persist for migrants, long after settling in new countries. Migrants use embodied practices from childhood to shape current cultural identities. Spaces that allow memories of past landscapes can build well-being in the present.